Growth hormone secretagogue receptor signalling affects high‐fat intake independently of plasma levels of ghrelin and LEAP2, in a 4‐day binge eating model. (2nd October 2019) - Cornejo, María Paula; Castrogiovanni, Daniel; Schiöth, Helgi B.; Reynaldo, Mirta; Marie, Jacky; Fehrentz, Jean‐Alain; Perello, Mario
Abstract: The growth hormone secretagogue receptor (GHSR) is a G protein‐coupled receptor that is highly expressed in the central nervous system. GHSR acts as a receptor for ghrelin and for liver‐expressed antimicrobial peptide 2 (LEAP2), which blocks ghrelin‐evoked activity. GHSR also displays ligand‐independent activity, including a high constitutive activity that signals in the absence of ghrelin and is reduced by LEAP2. GHSR activity modulates a variety of food intake‐related behaviours, including binge eating. Previously, we reported that GHSR‐deficient mice daily and time‐limited exposed to a high‐fat (HF) diet display an attenuated binge‐like HF intake compared to wild‐type mice. In the present study, we aimed to determine whether ligand‐independent GHSR activity affects binge‐like HF intake in a 4‐day binge‐like eating protocol. We found that plasma levels of ghrelin and LEAP2 were not modified in mice exposed to this binge‐like eating protocol. Moreover, systemic administration of ghrelin or LEAP2 did not alter HF intake in our experimental conditions. Interestingly, we found that central administration of LEAP2 or K‐(D‐1‐Nal)‐FwLL‐NH2, which are both blockers of constitutive GHSR activity, reduced binge‐like HF intake, whereas central administration of ghrelin or the ghrelin‐evoked GHSR activity blockers [D‐Lys3]‐GHRP‐6 and JMV2959 did not modify binge‐like HF intake. Taken together, current data indicate that GHSR activity in the brain affects binge‐like HF intake in mice independently of plasma levels of ghrelin and LEAP2.